Optimasi Viscosity Reducer dalam Mitigasi Minyak Mentah yang Mengental dari Sumur X - Nuzulia Rahma Yona; Budhi Oktavia (Lembaga Yasin AlSys, 2025)
Crude oil from Well X contains both hydrocarbon and non-hydrocarbon components, and during its transportation from Field D to Port E, it encounters technical challenges due to wax formation at low temperatures. This wax formation increases the crude oil’s viscosity, complicating the pumping process and raising operational costs. This study aims to reduce the viscosity of crude oil by injecting a chemical viscosity reducer at various doses: 0 ppm, 500 ppm, 1000 ppm, 1500 ppm, and 2000 ppm. The method involved viscosity testing following the addition of the chemical viscosity reducer at each dose level. The results indicate that the optimal dose is 2000 ppm, which successfully reduces the average viscosity from 604 cP to 313 cP. This reduction is attributed to the interaction of non-polar compounds in the chemical viscosity reducer that dissolve wax and inhibit paraffin crystallization, as well as polar compounds that disperse asphaltene molecules. These findings demonstrate the effectiveness of chemical viscosity reducers in enhancing crude oil transport performance and operational efficiency, particularly under low-temperature environmental conditions.